2(x+1)-3(y-1)=10 2(x+1)+3(y-1)=30
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 22:02:07
2(x+1)-3(y-1)=102(x+1)+3(y-1)=302(x+1)-3(y-1)=102(x+1)+3(y-1)=302(x+1)-3(y-1)=102(x+1)+3(y-1)=302(x+
2(x+1)-3(y-1)=10 2(x+1)+3(y-1)=30
2(x+1)-3(y-1)=10 2(x+1)+3(y-1)=30
2(x+1)-3(y-1)=10 2(x+1)+3(y-1)=30
2(x+1)-3(y-1)=10 ①
2(x+1)+3(y-1)=30 ②
② - ① ,可得
6(y-1) = 20
y-1=10/3
y=1+10/3 = 13/3
将 y=13/3 代入①式,可得
x=9
即x=9 ,y=13/3
x=9 y=23
2(x+1)-3(y-1)=10
2(x+1)+3(y-1)=30
两式相加 4(x+1)=40 x+1=10 x=9
x=9 代入 20-3(y-1)=10
3(y-1)=10
y=13/3
若2/x-1/y=3,求[y/x-y/x-y(x-y/x-x+y)]/x-2y/x的值
{4x-3y-10=0 3x-2y=0,{3x-4(x-y)=2 2x-3y=1,{2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
(3x-y)^2+(3x+y)(3x-y),x=1,y=-2
二元一次方程 :2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
变量x,y满足约束条件,x+y>=3,x-y>=-1,2x-y
(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
函数,y=3x/(x^2+x+1) ,x
函数y=3x/(x^2+x+1) (x
x-y/7 - x+y/10 =1/2 2(x-y)-5(x+y)=3修改、、、、(x-y)/7-(x+y)/10=1/2 2(x-y)-5(x+y)=3
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?
{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?
10X+Y+1/3Z=10Y+X 10X+Y+2/3Z=100X+Y
解方程组:(x+3)(y-2)=(x-3)(y+10),(x+1)(y+3)=(x-2)(y+12)
解方程:(x+3)(y-2)=(x-3)(y+10) (x-1)(y+3)=(x+2)(y+12)
{ x-y/7-x+y/10=1/2 {2(x-y)+5(x+y)=3